A study of the tragedy of Coriolanus by William Shakespeare - Knox, Catherine Mary (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1973)
It would be difficult to prove conclusively that Shakespeare was not invited or requested to write a play based on the popular story of Coriolanus. J.M. Robertson concretises this possibility with an intriguing thesis that the play was in fact rewritten from an original by Chapman. The story, he argues, would have had a far greater appeal to Chapman with his consuming interest in the heroic age of Classical antiquity, than to Shakespeare. Further, it is likely, he says, that Chapman was familiar with Alexandre Hardy 's Coriolan which, it is generally accepted, Shakespeare was not, hence the startling similarities in some of the two plays' deviations from their common source. This is hardly a more satisfactory explanation than the kind of airy alternative that disposes of the mystery by saying the source material is such that it would invite any dramatist to make similar changes. Chap. 1
Keywords: Shakespeare, William, 1564-1616 -- Coriolanus; Shakespeare, William, 1564-1616 -- Criticism and interpretation